Effects of stress on lithium transport in amorphous silicon electrodes for lithium-ion batteries. (April 2015) - Pan, Jie; Zhang, Qinglin; Li, Juchuan; Beck, Matthew J.; Xiao, Xingcheng; Cheng, Yang-Tse
Abstract: Silicon, as a promising electrode material for high energy density lithium ion batteries, experiences large strains and stresses during lithiation and delithation. The coupling effect between stress and lithium diffusion leads to a grand challenge to optimizing the design of Si electrodes with high capacity and high rate capability, particularly considering the amorphization of Si during initial cycles. In this study, we established a relationship between stress and the diffusion coefficients of Li in amorphous Si by ab initio molecular dynamics calculations (AIMD). The prediction from AIMD was validated by the potentiostatic intermittent titration measurements. Our results showed that two Li diffusion mechanisms can operate depending on the stress state. Specifically, the stress can increase Li diffusion either through increasing free volume under tension or by changing local structure under compression. However, within the range of stress generated during the lithiation and delithation process, diffusion coefficients are expected to vary by only one order of magnitude. Graphical abstract: Highlights: Both simulation and experiment demonstrated that Li diffusivity varies by less than one order of magnitude in stressed Si electrodes. Stress can increase Li diffusion either through increasing free volume under tension or by changing local structure under compression. Compressive stress can facilitate Li diffusion by changing Li local structure.